Testing the Drosophila maternal haploid gene for functional divergence and a role in hybrid incompatibility. - Castillo, D.M.; McCormick, B.; Kean, C.M.; Natesan, S.; Barbash, D.A. (G3 : genes - genomes - genetics, 2022)
Crosses between Drosophila simulans females and Drosophila melanogaster males produce viable F1 sons and poorly viable F1 daughters. Unlike most hybrid incompatibilities, this hybrid incompatibility violates Haldane's rule, the observation that incompatibilities preferentially affect the heterogametic sex. Furthermore, it has a different genetic basis than hybrid lethality in the reciprocal cross, with the causal allele in Drosophila melanogaster being a large species-specific block of complex satellite DNA on its X chromosome known as the 359-bp satellite, rather than a protein-coding locus. The causal allele(s) in Drosophila simulans are unknown but likely involve maternally expressed genes or factors since the F1 females die during early embryogenesis. The maternal haploid (mh) gene is an intriguing candidate because it is expressed maternally and its protein product localizes to the 359-bp repeat. We found that this gene has diverged extensively between Drosophila melanogaster and Drosophila simulans. This observation led to the hypothesis that Drosophila melanogaster mh may have coevolved with the 359-bp repeat and that hybrid incompatibility thus results from the absence of a coevolved mh allele in Drosophila simulans. We tested for the functional divergence of mh by creating matched transformants of Drosophila melanogaster and Drosophila simulans orthologs in both Drosophila melanogaster and Drosophila simulans strains. Surprisingly, we find that Drosophila simulans mh fully complements the female sterile phenotype of Drosophila melanogaster mh mutations. Contrary to our hypothesis, we find no evidence that adding a Drosophila melanogaster mh gene to Drosophila simulans increases hybrid viability.